Esophageal cancer revealing a tracheal diverticulum - Zhang, Miao; Wang, Heng; Wu, Wen-Bin; Zhang, Hui (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Tracheal diverticulum is a benign entity characterized by single or multiple invaginations of the tracheal wall, and is rarely encountered in clinical practice but frequently in postmortem examination as an incidental finding. Its combination with esophageal cancer is extremely rare. In this case report, we present a patient with these two lesions and analyze their correlation.